Discovery of Tyk2 inhibitors via the virtual site-directed fragment-based drug design. Issue 18 (15th September 2015) - Jang, Woo Dae; Kim, Jun-Tae; Son, Hoon Young; Park, Seung Yeon; Cho, Young Sik; Koo, Tae-sung; Lee, Hyuk; Kang, Nam Sook
Graphical abstract: Abstract: In this study, we synthesized compound12 with potent Tyk2 inhibitory activity from FBDD study and carried out a cell-based assay for Tyk2/STAT3 signaling activation upon IFNα5 stimulation. Compound12 completely suppressed the IFNα5-mediated Tyk2/STAT3 signaling pathway as well as the basal levels of pSTAT3. Stimulation with IFNα/β leads to the tyrosine phosphorylation of the JAK1 and Tyk2 receptor-associated kinases with subsequent STATs activation, transmitting signals from the cell surface receptor to the nucleus. In conclusion, the potency of compound12 to interrupt the signal transmission of Tyk2/STAT3 appeared to be equivalent or superior to that of the reference compound.